1989
DOI: 10.1111/j.1600-0722.1989.tb01620.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different caries preventive measures in children highly infected with mutans streptococci

Abstract: – The caries preventive effect of topical application of fluoride varnish (Duraphat), ferric‐aluminum‐fluoride solution (FeAlF) and chlorhexidine gel was compared in a 2‐yr clinical study. Children with more than 106 mutans streptococci per ml saliva were selected and a total of 189 13‐yr‐old children participated in the study. The children in the fluoride groups were treated every third month with either Duraphat or FeAlF‐solution. In the chlorhexidine group children with more than 2.5 × 105 mutans streptoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 19 publications
2
28
0
1
Order By: Relevance
“…After three years, the children in the control group had developed 9.6 new caries lesions, while the treated children only developed 4.2 new caries lesions (a 56% difference). Emilson's conclusions were also based on the original study by Linquist and others, 16 in which a 52% caries reduction was found in the 1% chlorhexidine gel group after two years, compared to the control group. In the chlorhexidine group, children with high levels of mutans streptococci in saliva were treated with 1% chlorhexidine gel every third month.…”
Section: Gelsmentioning
confidence: 99%
“…After three years, the children in the control group had developed 9.6 new caries lesions, while the treated children only developed 4.2 new caries lesions (a 56% difference). Emilson's conclusions were also based on the original study by Linquist and others, 16 in which a 52% caries reduction was found in the 1% chlorhexidine gel group after two years, compared to the control group. In the chlorhexidine group, children with high levels of mutans streptococci in saliva were treated with 1% chlorhexidine gel every third month.…”
Section: Gelsmentioning
confidence: 99%
“…The primary reason for this lack of effect may be the result of the high caries activity of this population. Other studies have found that fluoride varnishes work best in cases of mild to moderate caries activity [Koch and Petersson, 1975;Modéer et al, 1984;Lindquist et al, 1989]. Another factor contributing to the small effect of fluoride may be related to the intensity of application.…”
Section: Discussionmentioning
confidence: 99%
“…The median number of mutans streptococci was 8.4E10 5 colony forming units per milliliter (range 5.2E10 5 to 2.5E10 6 ), analyzed in stimulated whole saliva according to Lindquist et al [1989]. The DMFS (decayed, missed and filled tooth surfaces) index varied between 12 and 96 (mean 47).…”
Section: Subjectsmentioning
confidence: 99%